Periodontal disease and cancer patients undergoing chemotherapy. (2nd September 2014) - Vozza, Iole; Caldarazzo, Vito; Polimeni, Antonella; Ottolenghi, Livia
<x xml:space="preserve">Abstract</x> Objective The aim of this study was to evaluate periodontal status after periodontal treatment in patients with different malignant solid tumours submitted to chemotherapy. Methods Fifty‐four patients with newly diagnosed early‐stage solid tumour malignancy treated by surgery and eligible for adjuvant chemotherapy were enrolled in this study. Clinical periodontal parameters obtained by a single calibrated examiner were evaluated before chemotherapy (T0), 21 days after chemotherapy (T1) and 210 days after chemotherapy (T2). Patients were grouped into healthy or periodontally diseased subjects. All patients received oral hygiene instructions, and the diseased patients received periodontal treatment at baseline. Comparisons between the groups were performed using the McNemar test (P > 0.05) and the Wilcoxon test with Bonferroni correction (P < 0.02) using spss software. Results Of 54 patients enrolled in the study, two did not present to the third assessment (T2). The prevalence of periodontitis was 35.2% at baseline and no significant difference was found in the follow‐up assessments. There was a statistically significant reduction in probing depth (PD), plaque index (PI) and bleeding on probing (BOP) between baseline and follow‐up assessments. The attachment level (AL) did not vary significantly between the different follow‐up periods (P ≥ 0.06). Conclusions Periodontal treatment was effective in reducing PI, BOP and PD and in maintaining AL in periodontitis cancer patients undergoing chemotherapy.